Potential application of overseas forest biomass supply chain experience to reduce costs in emerging Australian forest biomass supply chains – a literature review. Issue 1 (2nd January 2019) - Strandgard, M.; Turner, P.; Mirowski, L.; Acuna, M.
ABSTRACT: Forest biomass (FB) is widely used overseas as an industrial energy source, particularly in Europe, but is currently little used in Australia. Typical attributes of FB disadvantage it as a fuel relative to traditional energy sources: high moisture content, low bulk density, spatial and temporal dispersion, low value and low energy content. As such, minimising FB delivered costs will be critical to further development of Australian forest biomass supply chains (FBSC). The paper reviews published international and Australian research into the key FBSC elements (biomass source, primary transport, storage, secondary transport and processing) focussing on areas where Australian FBSCs could potentially apply the research to reduce costs and where additional Australian research is required. Logging residue (LR) was identified as the FB resource in Australia with the greatest potential for use as biofuel. Rapid infield drying of LR in Australian studies suggests that infield drying could be used to reduce secondary transport costs, which can be a significant part of the delivered FB costs. However, further development of Australian FBSC models supported by research into primary and secondary transport costs, drying and chipper performance will be required to identify trade-offs between potential FBSC costs and benefits and to facilitate forest managers' decision-making processes regarding the establishment and running of FBSCs.